2019
DOI: 10.4108/eai.25-1-2019.159348
|View full text |Cite
|
Sign up to set email alerts
|

Forget the Myth of the Air Gap: Machine Learning for Reliable Intrusion Detection in SCADA Systems

Abstract: Since Critical Infrastructures (CIs) use systems and equipment that are separated by long distances, Supervisory Control And Data Acquisition (SCADA) systems are used to monitor their behaviour and to send commands remotely. For a long time, operator of CIs applied the air gap principle, a security strategy that physically isolates the control network from other communication channels. True isolation, however, is difficult nowadays due to the massive spread of connectivity: using open protocols and more connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The results revealed that the proposed model has the capacity to improve accuracy and recall and reduce false positive rate (FPR) while achieving the highest detection rates for unknown attacks. With F-1 values of 99% and 96% for Random Forest (RF) and Bidirectional Long Short-Term Memory (BLSTM), [18] concluded that RF and BLSTM successfully identify intrusions on SCADA systems. The study also suggests that standard intrusion detection systems cannot detect assaults that are not currently in their databases.…”
Section: Related Workmentioning
confidence: 99%
“…The results revealed that the proposed model has the capacity to improve accuracy and recall and reduce false positive rate (FPR) while achieving the highest detection rates for unknown attacks. With F-1 values of 99% and 96% for Random Forest (RF) and Bidirectional Long Short-Term Memory (BLSTM), [18] concluded that RF and BLSTM successfully identify intrusions on SCADA systems. The study also suggests that standard intrusion detection systems cannot detect assaults that are not currently in their databases.…”
Section: Related Workmentioning
confidence: 99%
“…The limitations of the selected supplier are some deficiencies in the tendering and project implementation phases, such as Factory Acceptance Test facilities (FAT), response speed, and training for operational and maintenance staff. Other framework was introduced in R. Lopez Perez et al, F. Adamsky et al R. Sousa, and T. Engel 7 to defend a Supervisory Control and Data Acquisition (SCADA) approach opposed to outbursts utilizing Machine learning (ML) techniques. Their work concentrated on assessing ML performance in identifying anomalies in SCADA structures.…”
Section: Relevant Studiesmentioning
confidence: 99%